2020
DOI: 10.3389/fnmol.2020.00160
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in Alzheimer’s Disease: Function and Potential Applications as Diagnostic Biomarkers

Abstract: Alzheimer's disease (AD) is the most common form of dementia. Although the incidence of AD is high, the rates of diagnosis and treatment are relatively low. Moreover, effective means for the diagnosis and treatment of AD are still lacking. MicroRNAs (miRNAs, miRs) are non-coding RNAs that play regulatory roles by targeting mRNAs. The expression of miRNAs is conserved, temporal, and tissue-specific. Impairment of microRNA function is closely related to AD pathogenesis, including the betaamyloid and tau hallmark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 188 publications
0
56
0
2
Order By: Relevance
“… 4 Recently, aberrant changes in miRNAs have been discovered to participate in AD progression, and are considered candidate blood-based biomarkers of AD, as they have been found to guide the clinical diagnosis of AD. 5 , 6 Wang et al 7 reported that the expression levels of miR-433 were reduced in AD patients and that this miRNA has the potential to be a therapeutic target through improving Aβ-induced neurotoxicity. Yang et al 8 provided evidence for miR-133b to serve as a diagnostic biomarker of AD and revealed its neuroprotective role, which is exerted through maintenance of neuronal viability.…”
Section: Introductionmentioning
confidence: 99%
“… 4 Recently, aberrant changes in miRNAs have been discovered to participate in AD progression, and are considered candidate blood-based biomarkers of AD, as they have been found to guide the clinical diagnosis of AD. 5 , 6 Wang et al 7 reported that the expression levels of miR-433 were reduced in AD patients and that this miRNA has the potential to be a therapeutic target through improving Aβ-induced neurotoxicity. Yang et al 8 provided evidence for miR-133b to serve as a diagnostic biomarker of AD and revealed its neuroprotective role, which is exerted through maintenance of neuronal viability.…”
Section: Introductionmentioning
confidence: 99%
“…Another area of interest are miRNAs that regulate MAPT affecting tau accumulation and relevant protein kinases affecting tau phosphorylation [ 68 , 69 ], looking at both of the distinct neuropathologies associated with AD. In-depth reviews of other miRNAs currently associated with AD have been expanded on elsewhere [ 61 , 70 , 71 ], however, further studies will be required to assess if a panel of miRNA biomarkers is sufficient to be clinically and diagnostically useful in the identification of AD patients, discerning AD patients from other neurodegenerative disease, or to monitor the progression of AD.…”
Section: Alzheimer’s Diseasementioning
confidence: 99%
“…It exceeds the purpose of this paper to describe the functions and potential applications of the numerous miRNAs in terms of diagnostic biomarkers since comprehensive reviews have been already written for AD [ 26 , 27 , 28 ] and PD [ 29 , 30 , 31 ], amyotrophic lateral sclerosis (ALS) [ 29 , 30 , 31 , 32 ], multiple sclerosis (MS) [ 33 , 34 ], traumatic brain injury (TBI) [ 35 , 36 ], or development-related syndromes, such as autism spectrum disorder (ASD) [ 37 , 38 ]. Instead, both in the central nervous system (CNS) and in the cerebral spinal fluid (CSF), miRNAs recruitment has boosted a novel impulse for the prognosis but, more strikingly, for neural regenerative medicine, shedding light on feasible translational brain applications that fill the present gap of clinical interventions represented by NSC transplantation.…”
Section: Mirnas Bridging Stemness and Cell Death In Neurogenesismentioning
confidence: 99%